The efficiency of mangosteen peel for dye removal - C Phawachalotorn; N Suwanpayak (My University, 2021)
Abstract Mangosteen peel, an agricultural waste to be used as an adsorbent, was prepared by a simple and eco-friendly method. The dried mangosteen peel (DMP) was initially studied its surface charge by using the pH drift method. The adsorption experiments were performed using the batch technique to explore the efficiency of methylene blue (MB) removal. Fourier Transform Infrared (FTIR) spectroscopy and Field Emission Scanning Electron Microscopy (FE-SEM) were used to characterise the DMP before and after the adsorption process. The results revealed that MB could be adsorbed onto the DMP surface via the electrostatic interaction between the cationic dyes and surface functional groups of the DMP. To explore the MB adsorption efficiency of DMP adsorbent, the factors of the initial pH of MB solution, particle sizes of the DMP, DMP dosage, and contact time were investigated by using Ultraviolet-Visible (UV-Vis) spectrophotometer. It was found that the percentage of MB removal was 99.7% by using 5 g/L of DMP at particle sizes of lower than 75 μm within ten minutes under the initial pH condition of MB solution. Moreover, the experimental equilibrium adsorption data were fitted to the Freundlich isotherm model with R 2 = 0.9869.
Keywords: Methylene blue; Cationic polymerization; Adsorption and biosorption for pollutant removal